Food Security Futures: some comments from a Brazilian perspective - Martha, Geraldo (2013)
Perspectives on the Future of Food Security, Review 1 by Geraldo Martha, EMBRAPA on 11 April 2013 at the Food Security Futures I Conference in Dublin, Ireland.